Feasibility Study of Belitung Hotel Project (Case Study PT XYZ) - Arsanti, Meutia; Murtaqi, Isrochmani (Journal of Business and Management, 2014)
This research will focus on tourism and hospitality business. For example is the hotel project of PT XYZ in Belitung. The purpose of this study is to gain feasibility of Belitung hotel project and determine whether the project is a good foundation for PT XYZ by knowing the return of the project of 10 years and after, required payback period in economic lifetime of 10 years, profitability index and internal rate of return as a decision rule for consideration in decision making management. To define the return of the project, author will be using the cash flow of the project. This project also assumed that the project will be continued and growing forever thatâ€™s why to determine terminal value of the project is a must. After calculating the cash flow and terminal value of the project the study found that the Net Present Value of the project generates a positive value of Rp 1,362,042,391,704 if PT XYZ continuing to operate the business forever. The profitability index of the project shows result of 9.5 with project Internal Rate of Return of 43.7% and the Modified Internal Rate of Return of this project is 55.5%. The Payback Period of the project is 5 years and 2 months and Discounted Payback Period this project is 5 years and 5 month. The safety number on occupancy rate can be a minimum standard and indicate the situation of the hotel operation. Net Present Value of theproject using safety occupancy rate generates a positive value of Rp 2,512,004,324,803 with the profitability index of the project showing result of 21.5. The Internal Rate of Return of the project is 101.4% and Modified Internal Rate of Return of this project using safety occupancy rate is 103.5%. The Payback Period of the project is 1 years and 7 months and the result of Discounted Payback Period is 1 years and 8 month. Based on the conclusion obtained from the analysis of the data author conclude that implementing Belitung hotel project is feasible and recommended for PT XYZ so they can increase firm wealth.Â Keywords: Belitung, Tourism, Hotel, Feasibility Study, Cash flow, terminal valueCategory : Finance, Business Plan